2018
DOI: 10.1007/s10209-018-0638-0
|View full text |Cite
|
Sign up to set email alerts
|

Game-playing as an effective learning resource for elderly people: encouraging experiential adoption of touchscreen technologies

Abstract: Elderly people often struggle to keep up with digital advancements, particularly given the fast pace of such developments and the increasing need to interact with novel devices in everyday life. To include elderly people in ongoing socio-technological developments, we aim to overcome the barriers to learning and adoption such older adults may face. In this contribution, we set the methodological stage for an interactive game-playing approach using touchscreen tablets. By using games in learning settings, we en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 34 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…Participants with CGE reported fewer technical difficulties and expressed greater intention to use virtual technologies in the future. The finding has been supported by numerous studies examining participants of all ages (Baek et al ., 2020; McColgan et al ., 2018; Oppl & Stary, 2018). Practical experience in any skill raises self‐efficacy in that skill, leading to improved performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants with CGE reported fewer technical difficulties and expressed greater intention to use virtual technologies in the future. The finding has been supported by numerous studies examining participants of all ages (Baek et al ., 2020; McColgan et al ., 2018; Oppl & Stary, 2018). Practical experience in any skill raises self‐efficacy in that skill, leading to improved performance.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Akcaoglu and Kale (2016) reported a case study of a teacher who, following a game‐design workshop, reported high comfort with technology combined with rapid acquisition of the relevant technological abilities. Another recent study indicated that playing digital games can assist the elderly to acquire digital abilities (Oppl & Stary, 2018). Experiences with computers in general and computer games in particular are associated with high self‐efficacy in computer use (Hatlevik, Throndsen, & Gudmundsdottir, 2018).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…This means, collaborative work is needed in the teaching and learning networks, teachers must learn from their students, and vice versa, thus becoming another student, the principle of digital academic retribution is exercised. Much of the current evidence affirms that digital competences allow professional development, although some studies have shown this, achieving that a small percentage of the population acquires these possibilities if these skills are in a formative gap (Guizado et al, 2019;Pozos & Tejada, 2018;Oppl & Stary, 2018). Therefore, we can affirm that digital competences are inherent competences in 122 the social development that is sought today, since technologies, virtual media and artificial intelligence become necessary elements to achieve that students immerse themselves in digital communities, but above all, empower yourself to captivate others in these environments.…”
Section: Digital Competences: Findings and Perspectivesmentioning
confidence: 99%
“…The study is an international collaborative effort between researchers in UK, Austria, North Macedonia, and Slovenia, each having slightly different priorities in the needs and context of both learners and the availability of mentors to support the learning development. We based our objectives on previous research within the project [5], where the participants were single users, only smaller touch-based devices were used, the monitoring was performed remotely, and reporting was only on error behaviour.…”
Section: Motivationmentioning
confidence: 99%